Calidad del cuidado enfermero percibida por los usuarios de medicina interna del Hospital General Isidro Ayora, periodo mayo 2019-abril 2020 - Cruz Caraguay, Diana Isabel (2020)
Nursing professionals have a large percentage of the human resources available to provide health services, from the user's admission to their progress; In accordance with the aforementioned, the study focused on determining the quality of nursing care perceived by internal medicine users of the General Hospital Isidro Ayora, period May 2019 - April 2020; the approach was quantitative, descriptive scope and cross section; the sample consisted of 303 patients, their confidence level is 95%, with a margin of error of 5%. The technique used was the survey to achieve the specific objectives set and the CUCACE questionnaire (version in Spanish) was specified as a reference for the collection of information. The results obtained, related to the sociodemographic characteristics, determined that the predominant sex is women, in the age range the group over 65 years old, at the higher education level and at the time of hospitalization 82% had a hospital stay of 1 to 4 days. In the quality of nursing care perceived by users, 83% determined it to be excellent; Regarding the dimension of experience, the results obtained are satisfactory reaching 93%, as well as satisfaction with 84%, therefore in relation to the total responses, the frequency of negative manifestations is minimal. Key words: Satisfaction, experience, perception, patients